1999
DOI: 10.1111/j.1601-0825.1999.tb00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological understandings and mysteries of noma (cancrum oris)

Abstract: The microbiologic history of noma was reviewed. Studies have associated the disease process with large numbers of fusiform bacilli and spirochetal organismS. In order to study the microbiology of the staging and infection periods of noma 62 Nigerian children, aged 3–14 years, 22 children had acute necrotizing ulcerative gingivitis (ANUG) and were also malnourished, 20 exhibited no acute necrotizing ulcerative gingivitis but were malnourished and 20 were free of acute necrotizing ulcerative gingivitis and in go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
5

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 66 publications
1
57
0
5
Order By: Relevance
“…The primary reason for this obscurity is obvious: the epicenter of noma development, the oral cavity, is inhabited by several hundred species of normal commensal bacteria [48][49][50][51]. A long held notion is that noma is caused by spirochetes and fusobacteria [5,6,52]. This notion partly stems from an extrapolation of the microbiological culprits of the presumed noma antecedent, NUG, which also includes spirochetes and fusobacteria, and partly because the levels of these organisms appear to be elevated in noma.…”
Section: Microbiology Of Nomamentioning
confidence: 99%
See 1 more Smart Citation
“…The primary reason for this obscurity is obvious: the epicenter of noma development, the oral cavity, is inhabited by several hundred species of normal commensal bacteria [48][49][50][51]. A long held notion is that noma is caused by spirochetes and fusobacteria [5,6,52]. This notion partly stems from an extrapolation of the microbiological culprits of the presumed noma antecedent, NUG, which also includes spirochetes and fusobacteria, and partly because the levels of these organisms appear to be elevated in noma.…”
Section: Microbiology Of Nomamentioning
confidence: 99%
“…Nevertheless, recent reports suggest that noma is caused by a mixed infection of oral and extraoral opportunistic pathogens [3,5,6,54] while incorporating the proposal that some noma cases may be the result of zoonotic infection with Fusobacterium necroforum. Using culture-independent molecular methods, Paster et al [54] reported the detection of 67 bacterial species or phylotypes in advanced noma lesion of four Nigerian patients.…”
Section: Microbiology Of Nomamentioning
confidence: 99%
“…It has been speculated that B�rrelia vincentii and F�s��acteri�� are prominent bacteria in such lesions. 2,8 Recent reports suggest that besides fusiform bacilli and spirochetes, other anaerobic bacteria are present in a relatively high proportion of noma lesions. 8 F. necr����r�� is considered a key component.…”
Section: Case Managementmentioning
confidence: 99%
“…2,8 Recent reports suggest that besides fusiform bacilli and spirochetes, other anaerobic bacteria are present in a relatively high proportion of noma lesions. 8 F. necr����r�� is considered a key component. This organism produces dermatotoxins, which could explain the rapid progression of the disease.…”
Section: Case Managementmentioning
confidence: 99%
See 1 more Smart Citation